Colaboração premiada na lei das organizações criminosas: uma análise dos “prêmios” concedidos a delatores e seus limites legais - Almeida, Francisco Franklin Júnior (Universidade Federal Rural do Semi-Árido, 2019)
The presente work aims to answer the follwing question: Prizes awarded to whistleblowers under the plea bargaining law disrespect cogent legal limits? The present work is justified in view of the importance of the theme at the moment, since it is the new law directly responsible for confrontation and punishment of true political-business criminal organizations that settled in the center of the Republic, causing huge damage to the public purse and to society. Many actions were opened, based on the collaboration of the so-called whistleblowers, who received legally agreed benefits, many of them according to most doctrine, they violated legal limits. Initially, it will be introduction and evolution of business criminal law in Brazil, as well as its introduction in our legal system. Afterwards, the Institute of Awarded Delation will be studied in several criminal acts, until we reach the law 12.850 / 2013, called law of the criminal organizations. Finally, some prizes awarded under the Operation Car Wash, in order to answer the initial question.
Artigo acadêmico
Keywords: Direito Penal Negocial; Colaboração Premiada; Operação Lava Jato; Violação de Leis Penais; Business Criminal Law; Plea Bargaining; Operation Lava Jato; Violation of Criminal Laws; CIENCIAS SOCIAIS APLICADAS::DIREITO